Effect of Household Cooking Energy Poverty on Child Respiratory Health in Pakistan - Qurat-ul-Ann, Abre- Rehmat; Mahfooz, Sana (iRASD Journal of Economics, 2022)
Household cooking energy poverty can lead to serious health concerns for the household members generally and children under age five specifically. To attain sustainable development goal 3 of ensuring healthy lives and promoting well-being for all of all ages, Pakistan has to strive for development in the child health sector. The recent pandemic has amplified the significance of this issue many folds. This study aims to identify the effect of household cooking energy poverty on the respiratory health of children under the age of five using Pakistan demographic and health survey data, 2017-18. 26.4 percent of the sample households are cooking energy poor in Pakistan. Child health is at greater risk in Balochistan and Gilgit Baltistan due to a greater multidimensional incidence of cooking energy poverty. Rural areas with a higher incidence of energy poverty are also vulnerable in terms of child wellbeing. Negative binomial regression analysis estimates the effect of household cooking energy poverty on number of children with respiratory issues in Pakistan. Empirical results suggest that a one-unit increase in household cooking energy poverty in Pakistan leads to a significant increase in the expected log (count) of number of children with respiratory infection by 0.21. Household cooking energy poverty directly affects respiratory health of children under age five in Pakistan. The study recommends that through the development and adoption of the use of modern stoves and clean fuels, improvement in the indoor environment and health of children in Pakistan can be attained.